Utilization of the Weighted Product-Based CIPP Evaluation Model in Determining the Best Online Platform - Dewa Gede Hendra Divayana; P. Wayan Arta Suyasa; Nyoman Santiyadnya; Made Susi Lissia Andayani; I Made Sundayana; I Nengah Dasi Astawa; Ni Wayan Rena Mariani; Gusti Ayu Dessy Sugiharni (HighTech and Innovation Journal, 2023)
Since the COVID-19 pandemic, there have been many free online platforms that can be used to support the online learning process at health colleges in Bali. However, it is difficult to determine the best online platform from the various choices of free online platforms that are scattered on the internet. Therefore, it needs innovations that contribute to helping solve these problems. One model as an innovation that can be used and contributes to solving problems is the Weighted Product-based CIPP evaluation model. The model needs to be measured for the quality of its calculations to ensure success in determining the best online platform. Therefore, this research aimed to show the quality of the Weighted Product method calculation integrated with the CIPP (Context-Input-Process-Product) model in determining the best platform used in health colleges during the COVID-19 pandemic. The instrument used to assess the quality of that calculation was a questionnaire consisting of eight questions. The subjects involved in the assessment were 20 experts. The research was carried out at several health colleges in Bali. The analytical technique used in analyzing the research data was descriptive-quantitative. The analysis was carried out by comparing the quality percentage of the calculation simulation with the quality standard based on an eleven-point scale. The study results showed the quality percentage of calculation simulation was 87.250%, so it was included in the very good category. This research has a significant impact on the progress of the educational evaluation field through research findings in the form of the appearance of the combination of the Weighted Product method with the CIPP evaluation model. The novelty of this research is the combination of the Weighted Product method and the CIPPmodel, which makes it easier for educational evaluators to determine the best online platform that supports online learning during the COVID-19 pandemic and even post-COVID-19.